New data on habitat conditions and the state of japanese huchen Parahucho perryi population in Lake Lebedinoye (Iturup Island) - О. V. Zelennikov; R. A. Semenov (Известия ТИНРО, 2025)
Spatial distribution of fish species, in particular japanese huchen Parahucho perryi, was examined by fry seine (length 20.0 m, height 1.5 m, mesh size 4 mm in the belly) in Lake Lebedinoye in the period from May to December 2024. In total, 10 fish species were identified in the lake, the most common of which were amur stickleback Pungitius sinensis and juvenile chum salmon Oncorhynchus keta, always presented in the catches. The third numerous species was japanese dace Tribolodon hakonensis, which number in 2024 was almost four times less than in the year before. The salmon species competing with japanese huchen, as whitespotted char Salvelinus leucomaenis and juveniles and dwarf males of masu salmon Oncorhynchus masou, were caught occasionally. In summer, the lake were significantly overgrown with higher aquatic vegetation, both at the bottom and alongshore, though filamentous algae were not abundant and the phytoplankton blooming was not detected. The ichthyocenosis composition changed noticeably between May and August — juvenile chum salmon had gone, japanese smelt Hypomesus nipponensis became presented in each catch of seine net in the number > 10 ind. (up to 50–100 ind. per catch), and the number of japanese dace underyearlings increased many times. Japanese huchen were presented in noticeable quantity at least in the western and southern parts of lake where this species was captured in each towing. So, 20 ind. of huchen were caught in 18 catches obtained in May 20–27, of which 6 fish weighed 1.5–2.5 kg. Short-time migration of young chum salmon across the lake enhanced prominently the food supply for japanese huchen.